Tibial torsion and leg length discrepancy in idiopathic scoliosis among UTAR students - Khoo, Wan Qi (2022)
Background: Scoliosis may affect the bone anatomy and biomechanics of the lower extremity. Tibial torsion and leg length discrepancy are crucial anatomical characteristics in clinical setting. However, the prevalence of tibial torsion and leg length discrepancy in idiopathic scoliosis have not been reported. This study aimed to investigate the prevalence of tibial torsion and leg length discrepancy among idiopathic scoliosis. Methods: A cross-sectional study was conducted with 29 idiopathic scoliosis. Lower extremities assessment included tibial torsion and leg length discrepancy. Descriptive analysis was used to analyze participant characteristics and prevalence of tibial torsion as well as leg length discrepancy. Paired-samples T test was used to identify the mean difference of common thigh foot angle between both contralateral sides of the lower extremities. Results: The highest prevalence of torsion of tibia is internal tibial torsion with 58.6%, followed by 37.9% normal tibial torsion and 3.4% external tibial torsion. More males have abnormal tibial torsion than female. The number of participants with abnormal tibial torsion were found to be more in males on the left side and slightly more in females on the right side. The common thigh foot angle revealed in this study is 11.40°. There is no significant mean difference in common thigh foot angle between both contralateral sides of the lower extremities. Thigh foot angle for internal tibial torsion is likely prevalent on the left tibia. Only 1 out of 29 participants (3.4%) have true LLD. LLD is not likely prevalent in idiopathic scoliosis. Conclusion: The tibial torsion among idiopathic scoliosis was reported in this study especially the internal tibial torsion. Thigh foot angle is more likely prevalent on the left lower extremity and more on male group. Lower extremity screening should assist in the identification of tibial torsion and leg length discrepancy. This may then lead to early prevention of lower limb pathology. Future studies may conduct with larger sample size in relation to current study. Possible risks of high thigh foot angle in adolescent idiopathic scoliosis may conduct in future study.